1989
DOI: 10.1152/jappl.1989.66.4.1674
|View full text |Cite
|
Sign up to set email alerts
|

No effect of brain blood flow on ventilatory depression during sustained hypoxia

Abstract: Minute ventilation (VE) during sustained hypoxia is not constant but begins to decline within 10-25 min in adult humans. The decrease in brain tissue PCO2 may be related to this decline in VE, because hypoxia causes an increase in brain blood flow, thus resulting in enhanced clearance of CO2 from the brain tissue. To examine the validity of this hypothesis, we measured VE and arterial and internal jugular venous blood gases simultaneously and repeatedly in 15 healthy male volunteers during progressive and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
3

Year Published

1990
1990
1998
1998

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
5
22
3
Order By: Relevance
“…Extending these findings, Brown and Lawson (22) demonstrated an acidotic shift in brain stem extracellular fluid during the late ventilatory depression in neonatal piglets. Also, Suzuki et al (23) recently showed no differences in jugular venous Pco, (which was used as an index of brain tissue Pco2) between human adults with sustained and unsustained ventilatory response to hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Extending these findings, Brown and Lawson (22) demonstrated an acidotic shift in brain stem extracellular fluid during the late ventilatory depression in neonatal piglets. Also, Suzuki et al (23) recently showed no differences in jugular venous Pco, (which was used as an index of brain tissue Pco2) between human adults with sustained and unsustained ventilatory response to hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Qb(i)/Qb(2) was obtained from the Doppler data, and an assumed value of 8-7 mmHg for (Pb,co2 (1) -Pa,co2(1)) was used (Suzuki et al 1989) (see Discussion).…”
Section: Estimation Of Ventilation During Eucapnia and Hypercapniamentioning
confidence: 99%
“…(Pb,C02(2) -Pb,CO2 (01)) where, VE(1) and VE (2) are the values for expiratory ventilation during eucapnia and hypercapnia, respectively, and (Pb,co2(2) -Pb,c02 (1) Vb,CO2() (16) Equation (16) gives the change in Pb,co with hypoxia as a function of the ratio of blood flow in the euoxic and hypoxic conditions (obtained from the Doppler data) and the difference in PCO2 between brain tissue and arterial blood in euoxic eucapnia for which a value of 8-7 is assumed (Suzuki et al 1989) (again, see Discussion).…”
Section: Estimation Of Ventilation During Eucapnia and Hypercapniamentioning
confidence: 99%
See 2 more Smart Citations